Nitrogen-Fixing (Acetylene Redution) Activity and Population of Aerobic Heterotrophic Nitrogen-Fixing Bacteria Associated with Wetland Rice - Watanabe, Iwao (1979)
Nitrogen-fixing activity associated with different wetland rice varieties was measured at various growth stages by an in situ acetylene reduction method after the activities of blue-green algae (cyanobacteria) in the flood water and on the lower portion of the rice stem were eliminated. Nitrogen-fixing activities associated with rice varieties differed with plant growth stages. The activities increased with plant age, and the maximum was about at heading stage. The nitrogen fixed during the whole cropping period was estimated at 5.9 kg of N per ha for variety IR26 (7 days) and 4.8 kg of N per ha for variety IR36 (95 days). The population of aerobic heterotrophic N(2)-fixing bacteria associated with rice roots and stems was determined by the most-probable-number method, using semisolid glucose-yeast extract and semisolid malate-yeast extract media. The addition of yeast extract to the glucose medium increased the number and activity of aerobic heterotrophic N(2)-fixing bacteria. The glucose-yeast extract medium gave higher counts of aerobic N(2)-fixing bacteria associated with rice roots than did the malate-yeast extract medium, on which Spirillum-like bacteria were usually observed. The lower portion of the rice stem was also inhabited by N(2)-fixing bacteria and was an active site of N(2) fixation.